2020
DOI: 10.1038/s41586-020-2483-6
|View full text |Cite
|
Sign up to set email alerts
|

The tidal remnant of an unusually metal-poor globular cluster

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 57 publications
5
43
0
Order By: Relevance
“…These conditions are related to the minimum metallicity of observed globular clusters (GCs: Forbes et al 2018). Forbes et al (2018) showed the metallicity floor of GCs in the Milky Way with 𝑍 ∼ 10 −2.5 𝑍 (but see , Wan et al 2020). Recently Larsen et al (2020) observed the lower metallicity GC of 𝑍 ∼ 10 −2.9 𝑍 in Andromeda galaxy.…”
Section: Summary and Discussionmentioning
confidence: 93%
“…These conditions are related to the minimum metallicity of observed globular clusters (GCs: Forbes et al 2018). Forbes et al (2018) showed the metallicity floor of GCs in the Milky Way with 𝑍 ∼ 10 −2.5 𝑍 (but see , Wan et al 2020). Recently Larsen et al (2020) observed the lower metallicity GC of 𝑍 ∼ 10 −2.9 𝑍 in Andromeda galaxy.…”
Section: Summary and Discussionmentioning
confidence: 93%
“…Harris 1996Harris , 2010. However, dissolved, less massive GCs may have lower metallicities: the Phoenix stream likely consists of a single stellar population originating in a dissolved globular cluster of Z = 10 −2.7 Z (Wan et al 2020). Another example, the Sylgr stream, might be the remnant of another disrupted GC with stars of an even lower metallicity, Z = 10 −2.9 Z (Roederer & Gnedin 2019).…”
Section: Observational Signaturementioning
confidence: 99%
“…Ravi, Sylgr and Phoenix are thin streams with orbits similar to Indus. With little metallicity variation within either Sylgr or Phoenix (Ibata et al 2019;Wan et al 2020), these streams likely originate from globular clusters hosted by the progenitor of Indus and Jhelum.…”
Section: Association With Disrupted Galaxiesmentioning
confidence: 99%